The Effect Of The TPS (Think Pair Share) Learning Model Used By The Geogebra Application On The Ability Of Understanding Mathematical Concepts Of Grade X - Arianto Munthe; Lois Oinike Tambunan; Christa Voni Roulina Sinaga (CV Putra Publisher, 2025)
This study aims to determine the effect of the TPS (Think Pair Share) learning model assisted by the Geogebra application on the mathematical concept understanding ability of class X students of SMK Negeri 1 Siantar. The sampling technique used in this study is Probability Sampling. In this study, the type of experimental research used is Probability Sampling with a type of research design, namely One Shot Case Sturdy. In this type of design, the researcher will use a class unit where the researcher will provide a solution (treatment) to students for several periods. Based on the results of data analysis and discussion, it can be concluded that there is a positive and significant influence of the TPS (Think Pair Share) learning model assisted by the Geogebra application on the ability to understand mathematical concepts of class X students of SMK Negeri 1 Siantar. This influence can be seen from the regression equation Y = 63,570 + 1.271 with a regression coefficient of 1.271. Through the t-test, it can be seen that t_count>t_table = (11,361>6,742) indicates that significance and by using the coefficient of determination can be seen the magnitude of the influence is 82.2%.